A review of computational fluid dynamics for forced-air cooling process. (15th April 2016) - Zhao, Chun-Jiang; Han, Jia-Wei; Yang, Xin-Ting; Qian, Jian-Ping; Fan, Bei-Lei
Highlights: We review the fundamentals of applying CFD to precooling of fresh produce. We summarize the parameters used to analyze packaging performance. We review recent studies that focus on optimizing the design of fresh produce packaging. We discuss various challenging issues. Abstract: Optimizing the design of fresh produce packaging is vital for ensuring that future food cold chains are more energy efficient and for improving produce quality by avoiding chilling injuries due to nonuniform cooling. Computational fluid dynamics models are thus increasingly used to study the airflow patterns and heat transfer inside ventilated packaging during precooling. This review discusses detailed and comprehensive mathematical modeling procedures for simulating the airflow, heat transfer, and mass transfer that occurs during forced-air precooling of fresh produce. These models serve to optimize packaging design and cooling efficiency. We summarize the most commonly used parameters for performance, which allows us to directly compare the cooling performance of various packaging designs.